Electrostatic Agitation in Hydrometallurgical Solvent Extraction - Ibana, Don; Steffens, Marc (Society for Mining, Metallurgy, and Exploration Inc., 2008)
The use of mechanical agitation in solvent extraction (SX) provides limited capability to control droplet size, droplet size distribution, and droplet motion leading to poor mass transfer, inefficient phase separation, and formation of interfacial precipitates, and thus, a major limitation of the current SX technology. The use electrostatic agitation appears to circumvent these limitations but limited fundamental understanding of the technique, particularly at conditions that are relevant to hydrometallurgical applications, hinder the development of commercial applications of the technique. An attempt to address these issues showed that the nature of the applied field, the properties of the aqueous feed, as well as the properties of the solvent influence phase dispersion, indicating that optimisation of mass transfer in an electrostatically agitated solvent extraction requires a good compromise among these variables.